SEKSISME BAHASA ARAB DAN TANTANGAN PEMBELAJARAN BAHASA ARAB - Inayatur Rosyidah (UIN Maulana Malik Ibrahim Malang, 2019)
Arabic sexism can be seen from the Arabic grammar system it self supporting the formation of sexist language. Arabic sexism in education, especially religious education in the form of subject matter and the education process increasingly dwarf women from the inequality of the patriarchal system. To build a world of equitable education without gender inequality originating from language sexism is to create gender-friendly language, restructure the curriculum, and require a paradigmatic, egalitarian, flexible, and persuasive learning step from all parties, especially teachers as the spearhead of the learning process.